The drawing of the three - King, Stephen, 1947-; Hale, Phil. (New York : New American Library, 1989)
Roland is drawn through a mysterious door that hurtles him into, our world. He joins forces with young Eddie and the beautiful and brave Odetta Holmes in a savage war against underworld evil and otherworldly enemies.
Argument -- Prologue: the sailor -- The prisoner -- Shuffle -- The lady of shadows -- Reshuffle -- The pusher -- Final shuffle -- Afterword.
"A Plume book."
Maine author. Stephen King was lives in Bangor, Me. and Florida.
Keywords: Horror tales